A Euglycemic Glucose Clamp Study to Evaluate the Bioavailability of LY2963016 Relative to Insulin Glargine in Healthy Chinese Subjects. Issue 12 (19th August 2021) - Liu, Hui; Wang, Feng; Ji, Yongjia; Ma, Tianyang; Li, Hongying; Linnebjerg, Helle; Chua, Laiyi; Tham, Lai San; Yu, Yerong
Abstract: Insulin glargine (IGlar) and LY2963016 (LY IGlar) are long‐acting insulin analogs with identical primary amino acid sequences. We conducted a randomized, open‐label, 2‐treatment, 2‐period, crossover study in healthy Chinese subjects to evaluate the relative bioavailability of LY IGlar to IGlar and pharmacokinetic (PK) and pharmacodynamic (PD) characteristics of LY IGlar. Subjects (n = 58) were randomized to receive single subcutaneous doses (0.5 U/kg) of LY IGlar and IGlar with a ≥7‐day washout period between study treatments. Serum was collected before and up to 24 hours after dosing to assess PK characteristics. PD characteristics were assessed by euglycemic clamp up to 24 hours after dosing. Linear mixed‐effects models were used to fit the log‐transformed primary PK (maximum observed concentration and area under the concentration‐time curve from time 0 to 24 hours) and PD parameters (maximum glucose infusion rate and total amount of glucose infused during clamp period). The geometric least squares means ratios (90% confidence interval) of LY IGlar to IGlar for maximum observed concentration and area under the concentration‐time curve from time 0 to 24 hours were 0.961 (0.887‐1.04) and 0.941 (0.872‐1.01), respectively. The geometric least squares means ratios (90% confidence interval) of LY IGlar to IGlar were 0.91 (0.85‐0.98) for maximum glucose infusion rate and 0.89 (0.82‐0.97) for total amount of glucose infused during clamp period. LY IGlar demonstrated similarity to IGlar in PK and PD characteristics following single‐dose (0.5 U/kg) administration in healthy Chinese subjects.